Determination of the critical pitting temperature and the critical ion (Cl-) concentration inducing pitting of AISI 304L stainless steel in 0.5 M H2SO4 - Fuchs-Godec, Regina (Acta chimica slovenica, 2004)
Corrosion of AISI 304L stainless steel in aqueous solutions of 0.5 M H2SO4 + 0.01 M KCNS + x M NaCl was studied at different temperatures (25, 40, and 50 °C). The critical ion (Cl-) concentration (CIC) and the critical pitting corrosion temperature (CPT) were determined on the basis of characteristic corrosion parameters (icrit, ipass, Epp), which were obtained through potentiodynamic scanning experiments. The activation energy of the process wasfound to be equal to -42.0 (1 0.08 ) kJ mol-1. As the temperature increased, the pitting potential, Epp, was shifted towards more negative values linearly with the reciprocal of temperature, when the concentration of added NaCl was above the CIC. In contrast, at concentrations very close to theCIC, the straight lines changed slopes. This result may indicate of the approximate boundary between metastable pitting and the beginning of stable pitting.
Keywords: avstenitna jekla; elektrokemija; kloridi; koncentracija; korozija; temperatura